High Mountain Conservation in a Changing World - Catalan, Jordi; Ninot, Josep M.; Aniz, M. Mercè (Advances in Global Change Research, 2017)
This book aims to provide case studies and a general view of the main processes involved in the ecosystem shifts occurring in the high mountains, and to analyse the implications for nature conservation. Although case studies from the Pyrenees are preponderant, conclusions are aimed at any mountain range surrounded by highly populated lowland areas. The chapters give emphasis to approaches from environmental geography, functional ecology, biogeography, and paleoenvironmental reconstructions. The introductory and closing chapters summarize the main challenges that nature conservation may face in mountain areas under the environmental shifting conditions. This interdisciplinary book will appeal to researchers in mountain ecosystems, students and nature professionals. This book is open access under a CC BY license.